2014
DOI: 10.3168/jds.2013-7315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of d-α-tocopherol and dietary energy on growth and health of preruminant dairy calves

Abstract: To observe the effects of supplemental dietary d-α-tocopherol in relation to dietary energy on growth and immune status in dairy calves, 32 newborn Holstein bull calves were assigned to 1 of 4 treatments for 5 wk in a 2 × 2 factorial, randomized complete block, split-plot design. Calves received moderate growth (MG) or low growth (LG) all-milk dietary treatments, formulated to support daily gains of 0.5 or 0.25 kg/d, respectively, per the dietary energy recommendation for milk-fed calves according to the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 31 publications
4
31
0
1
Order By: Relevance
“…Calves fed milk replacer, however, consistently achieve serum 25(OH) D concentrations greater than 30 ng/mL (Nonnecke et al, 2009a(Nonnecke et al, , 2010 due to the high vitamin D content in commercial milk replacers, often 10-to 20-fold more than the current NRC recommendation (NRC, 2001). In contrast, milk-fed calves not provided supplemental vitamin D frequently have low circulating 25(OH) D concentrations (Rajaraman et al, 1997;Kreuger et al, 2014), often decreasing to levels that would be indicative of clinical deficiency in humans (≤10 ng/mL; Holick, 2009). Evans and Bishop (1922) were the first to identify vitamin E and its obligatory role in reproduction.…”
Section: Introductionmentioning
confidence: 89%
“…Calves fed milk replacer, however, consistently achieve serum 25(OH) D concentrations greater than 30 ng/mL (Nonnecke et al, 2009a(Nonnecke et al, , 2010 due to the high vitamin D content in commercial milk replacers, often 10-to 20-fold more than the current NRC recommendation (NRC, 2001). In contrast, milk-fed calves not provided supplemental vitamin D frequently have low circulating 25(OH) D concentrations (Rajaraman et al, 1997;Kreuger et al, 2014), often decreasing to levels that would be indicative of clinical deficiency in humans (≤10 ng/mL; Holick, 2009). Evans and Bishop (1922) were the first to identify vitamin E and its obligatory role in reproduction.…”
Section: Introductionmentioning
confidence: 89%
“…Pasteurized whole milk (PWM) is a common component in calf diets on commercial dairy farms in the United States, as producers seek to capture losses from waste milk. Recent literature, however, has suggested that PWM alone does not meet the vitamin A, D 3 , and E nutritional requirements of young calves and that these requirements are increased by increased growth rates and immune challenge (Krueger et al, 2014;Nonnecke et al, 2014). Suggested mechanisms by which vitamin A and D 3 metabolites affect growth and immunity include the targeting of nuclear receptors to affect cell differentiation, tissue development, and immune cell signaling (Hall et al, 2011;Nelson et al, 2012;Rhinn and Dollé, 2012), whereas vitamin E is an antioxidant that protects cell membrane unsaturated fatty acids from oxidative processes such as respiration and inflammation (Traber and Atkinson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings by Krueger et al. () that higher vit E supplementation in preruminant calves is associated with lower serum haptoglobin, a positive acute phase protein, do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 88%
“…Krueger et al. () reported increased α‐tocopherol demands of preruminant calves with 0.5 kg/day live weight gain and Nonnecke et al. () observed α‐tocopherol utilization in calves that achieved growth rates of 1.16 kg/day relative to calves fed maintenance requirements suggesting vit E to be a limiting nutrient for growth rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation